The cultural activity of the Jews in Egypt 1922-1956 (Journal of the College of Basic Education, 2022)
The cultural activity of the Jews in Egypt “1922-1956” was divided into three sections. The first section is the Jewish press. The Jews exercised their complete freedom to publish their newspapers and magazines without any restrictions. Their newspapers and magazines were characterized by the support and backing of the Zionist movement and the adoption of its proposals in establishing a national home for the Jews in Palestine. And its invocation of Jewish history and its affirmation of the unity of the Jews in all the world and the education of the importance of the Hebrew language and its care towards highlighting the Jewish specificity with its personality and its clear features in order to achieve its known goals in this regard.As for the establishment of Jewish cultural associations, they had a history in that as well, and these associations served the same orientation, as well as promoting the cultural reality of the Jews in general by holding seminars and awareness lectures for the members of the sect and the community as a whole to convey their voice and demonstrate their ability in creativity.Only a limited number of Jewish writers emerged during the period in question, led by Murad Faraj Lisha and Israel Wolfensohn. The first was integrated with Zionist thought and sought to employ his idea to serve his plans, so he paved the way to find a link between the Hebrew and Arabic language and the Jewish origins, which he tried to prove that they belong to the Arabian Peninsula. The second, who tried to confirm the kinship between Jews and Arabs, and that they are cousins ​​in his opinion.The Jews did not integrate with the Arab culture movement in Egypt because they were influenced by European culture, especially French, and it was the language adopted in their schools, newspapers, books, and even some of their cultural lectures. Their influence was minimal within their surroundings.However, it cannot be overlooked that despite the advanced Jewish cultural awareness, many Jews were not proficient in the Hebrew language, and therefore many of the activities of their community were to search for ways to advance them in this regard, through the establishment of cultural societies and the development of various linguistic works.